Heurs et malheurs du système universitaire libanais à l’heure de l’homogénéisation et de la marchandisation de l’enseignement supérieur - Jacques Kabbanji (Revue des Mondes Musulmans et de la Méditerranée)
This article analyzes the recent development of “market oriented universities” in Lebanon, which were designed to meet the increasing demand for higher learning. First, it will give a brief insight about the history of higher education in Lebanon, the foundation of private universities and the role of religious communities. The analysis of the funding of these universities reveals a growing financial burden on families, as well as the indirect involvement of the State to this trend. Finally, it shows the link between homogenization and globalization, and how international cooperation encourages these trends. In the oldest universities, these trends encounter resistance, which is a sign of crisis more than a sign of good health.